Hybrid methods for modelling advanced electromagnetic systems using unstructured meshes - Simmons, Daniel (2016)
The aim of this project is the conception, implementation, and application of a simulation tool for the accurate modeling of electromagnetic fields within inhomogeneous materials with complex shapes and the propagation of the resulting fields in the surrounding environment. There are many methods that can be used to model the scattering of an electromagnetic field, however one of the most promising for hybridisation is the Boundary Element Method (BEM), which is a surface technique, and the Unstructured Transmission Line Modeling (UTLM) method, which is a volume technique. The former allows accurate description of the scatterer's boundary and the field's radiation characteristics, but cannot model scattering by materials characterized by a non-uniform refraction index. The latter, on the contrary, can model a very broad range of materials, but is less accurate, since it has to rely on approximate absorbing boundary conditions. A method resulting in the hybridisation of BEM and UTLM can be used to construct a tool that takes into account both the interaction with non-uniform tissue and propagation in its environment. The project aims to describe in detail the implementation of the novel method, and deploy it in a heterogeneous distributed computing environment.